Implementasi Model Problem Based Learning (PBL) Terintegrasi Jigsaw untuk Meningkatkan Partisipasi Siswa pada Pembelajaran Akidah Akhlak - Rif’atul Maimanah; Afif Kholisun Nashohih (Lembaga Yasin AlSys, 2026)
Students’ active participation in Aqidah Akhlak learning plays an important role in deepening their understanding and application of moral values, but the learning process in Grade VII at MTs Ma’arif 1 Jombang is still dominated by the lecture method, causing students to tend to be passive. This study aims to describe the implementation of the Problem Based Learning (PBL) model integrated with the Jigsaw method and to analyze the increase in students’ active participation after its implementation. This study used Classroom Action Research (CAR) with the Kemmis and McTaggart model. Data were collected through observation, interviews, and documentation, and were then analyzed descriptively using quantitative and qualitative approaches. The results show that the implementation of PBL integrated with Jigsaw was able to increase students’ active participation in Aqidah Akhlak learning. In Cycle I, students’ active participation was still below 50%, categorized as very poor, whereas in Cycle II there was an increase, as indicated by students’ participation achievements in several categories, namely very good, good, fair, and poor. In detail, two students reached 100%, one student reached 97.5%, one student reached 92.5%, one student reached 80%, four students were in the range of 62.5%–72.5%, and one student reached 57.5%. The conclusion of this study emphasizes that integrating the PBL model with the Jigsaw method can serve as an effective learning strategy to increase students’ active participation in the Aqidah Akhlak subject. These findings provide practical implications for teachers in designing more collaborative, problem-based, and student-centered learning.